THE BOTANICAL EXPEDITION IN THE SCHOOL BOOKTEXTS IN COLOMBIA 1974-2008 - Soto Arango, Diana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
It is presented the analysis of the messages that have in implicitly way the school textbooks, of social sciences, in the basic primary and secondary education, on the imaginary ones who identify the cultural history of the colony, especially the modal to the Botanical expedition, inside the cultural movement of the Illustration, and the relation of this one with the American Independence. The analysis places inside the legislation of Colombia of three periods that understands the investigation. The method limits itself inside the current history-graphic of the social history of the compared education and its makes a concrete in the trend of analysis of school texts under the indicators of: conceptualization of the illustration and botanical expedition; relevancy of the expedition in the beginning of the science in Colombia and the links with the independence; figures of relevant scientists; contribution to the national identity, didactic activities. In the iconography there is established the typology of the figures of Mutis, collaborators and of plants. The results place in small relevancy in the contents and the iconography of the Botanical Expedition. In the conclusion it was found that in the periods of study they change the designs of the texts and the contents. Journal of Latin American Education History, botanical expedition, independence, enlightenment, Mutis.